Internalisasi Nilai Pemasaran Syariah dalam Praktik Bisnis Halal dan Pembentukan Kepercayaan Masyarakat (Studi Kasus UMKM Halal di Koperasi Pesantren Sunan Ampel Jombang) - Siti Nurun Nadhifah; Sulistyowati Sulistyowati; Ferdy Gunawan; Mohammad Febri Gunawan (MANABIS: Jurnal Manajemen dan Bisnis, 2026)
This study aims to analyze the process of internalizing the value of sharia marketing characteristics (theistic, ethical, realistic, humanistic) in the halal business practices of MSMEs of the Sunan Ampel Jombang Islamic Boarding School Cooperative and its impact on public trust in the midst of the halalwashing issue. A descriptive qualitative approach through in-depth case studies applied thematic manual analysis, internal sharia SWOT, as well as triangulation of data from kyai, santri, consumer interviews, field observations, and cooperative documentation. The results show that the internalization of values takes place organically through the culture of kyai, santri, with the most dominant ethical ethics manifested in QR code transparency, measurement mandates, and sidq promotion. This strengthens consumer trust through emotional loyalty and reputation resilience, despite the constraints of low student digital literacy and mass price competition. This study confirms pesantren as an incubator of authentic halal MSMEs, providing a contextual sharia marketing model for replication in similar ecosystems. This study recommends digital sharia workshops, inter-Islamic boarding school collaboration, the 7P sharia checklist, and the DSN-MUI e-commerce fatwa for replication in national Islamic boarding school cooperatives to strengthen the competitiveness of sustainable halal MSMEs.